Plastic closure of wounds in patients with ischemic form of diabetic foot syndrome. - Ivanova, Yu. V.; Klimova, O. M.; Prasol, V. O.; Korobov, A. M.; Mushenko, Ye. V.; Kiriienko, D. O.; Didenko, S. М. (Medicni Perspektivi, 2018)
In the work the analysis of the results of treatment of 48 patients with ischemic and neurotrophic forms of diabetic foot syndrome has been performed. All patients had diabetes mellitus and IV degree of ischemia by Fontaine. After carrying out revascularization operations, a complex treatment was used that included phototherapy, the phase closure of tissue defects with synthetic coating with the application of fibrin clot and plasma enriched with platelet growth factor, vacuum therapy of wounds, autodermoplastics by Tirsch, free autodermoplastics with split skin scar. The implementation of the developed tactics allowed to achieve complete wound healing in 91.7% of patients, partial healing – in 8.3% of patients and to avoid high amputations.